Amorphous black phosphorus: wet-chemical synthesis and atomic disordering-dependent electrocatalytic performance. (1st April 2022) - Sun, Zhaojian; Zhang, Bowen; Khurram, Muhammad; Yan, Qingfeng
Abstract: Although crystalline black phosphorus (c-BP) is attracting enormous interest in the past few years for a wide range of applications, studies on amorphous BP (a-BP) have been quite rare due to the difficulty in its controllable synthesis. The reason lies in that the elemental phosphorous precursor favors to form c-BP, which is the thermodynamically stable phase. Herein, we report a facile ethylenediamine intercalation-and- deintercalation strategy to realize gram-scale preparation of a-BP. The atomic disordering in a-BP can be handily tuned by controlling the reaction time. Interestingly, the a-BP demonstrates atomic disordering-dependent oxygen evolution reaction (OER) activity. The a-BP with higher atomic disordering delivers higher OER performance. Such enhanced OER activity is ascribed to more low-coordination sites and unpaired electrons which usually served as active sites, as verified by electrochemically active surface area measurement results and electron spin resonance. Density functional theory calculation further reveals the enhancement for OER activity is mainly attributed to boosting conversion from O* to OOH*. Our results not only create a controllable wet-chemical approach to scalable production of a-BP but provide insights into structure-property relationship and its underlying mechanisms.